Potential use of wild seaweed of Panjang Island, Banten origin as cultivation commodity - Awaludin, Syabilla Alaika; Hermawan, Dodi; Saifullah, Saifullah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Seaweed is a valuable fishery commodity with significant economic importance. On Panjang Island, only one type of seaweed is currently cultivated: Eucheuma cottonii, also known as Kappaphycus alvarezii. This research aims to identify the wild seaweed species found in the waters around Panjang Island and assess their potential for cultivation. The study was conducted using observational methods in May 2024 within the waters of Panjang Island, Serang Regency, Banten Province. Identification of the seaweed samples was carried out at the Aquaculture Laboratory of the Fisheries Study Program, Faculty of Agriculture at Sultan Ageng Tirtayasa University. Samples were collected from selected stations using the Purposive Random Sampling method. The results were compiled, presented in table form, and analyzed descriptively. Identification was accomplished using an identification book, the data center, and other relevant literature. The study identified 16 species of macroalgae, which included 5 species of red algae, 5 species of green algae, and 6 species of brown algae. Among these, 9 species have been cultivated, while 7 have yet to be cultivated in Indonesia. The wild seaweed species with potential for cultivation include Gracilaria coronopifolia, Gracilaria salicornia, Kappaphycus alvarezii, Ulva lactuca, Caulerpa lentillifera, Sargassum crassifolium, Sargassum polycystum, Sargassum cinereum, and Padina australis. Several of these species hold promise as potential cultivation commodities in the waters surrounding Panjang Island.